Drying and Film Formation Processes of Graphene Oxide Suspension on Nonwoven Fibrous Membranes with Varying Wettability - Zeman Liu; Jiaxing Fan; Jian Xue; Fei Guo (Surfaces, 2025)
Graphene oxide (GO) films have attracted significant attention due to their potential in separation and filtration applications. Based on their unique lamellar structure and ultrathin nature, GO films are difficult to maintain in a free-standing form and typically require substrate support. Consequently, understanding their film formation behavior and mechanisms on substrates is of paramount importance. This work employs commonly used nonwoven fibrous membranes as substrates and guided by the coffee-ring theory, systematically investigates the film formation behaviors, film morphology, and underlying mechanisms of GO films on fibrous membranes with varying wettability. Fibrous membranes with different wetting properties—hydrophilic, hydrophobic, and superhydrophobic—were prepared via electrospinning and initiated chemical vapor deposition (iCVD) surface modification techniques. The spreading behaviors, deposition dynamics, capillary effects, and evaporation-induced film formation mechanisms of GO suspensions on these substrates were thoroughly examined. The results showed that GO formed belt-like, ring-like, and circular patterns on the three fibrous membranes, respectively. GO films encapsulated more than the upper half, approximately the upper half, and the top portion of fibers, respectively. Pronounced wrinkling of GO films was observed except for those on the hydrophilic fibrous membrane. This work demonstrates that tuning the wettability of fibrous substrates enables precise control over GO film morphology, including fiber encapsulation, wrinkling, and coverage area. Furthermore, it deepens the understanding of the interactions between 1D nanofibers and 2D GO sheets at low-dimensional scales, laying a foundational basis for the optimized design of membrane engineering.